A Case Study Of E-Learning In Corporation And Prototype Development. - Hean, Tan Tee (2001)
The objective of this research report will focus on major critical factors of E-learning system that a corporation needs to take into consideration. Based on a user readiness of E-Learning survey, result is being further analyzed and concludes by recommending some basic application for E-learning in corporation. A prototype is being developed based on the E-learning conceptual framework to demonstrate a typical corporate E-learning implementation.